2023
DOI: 10.1021/jacs.3c10179
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining from Agriculturally Relevant Fungi Led to a d-Glucose Esterified Polyketide with a Terpene-like Core Structure

Chunsheng Yan,
Wenyu Han,
Qingyang Zhou
et al.

Abstract: Comparison of biosynthetic gene clusters (BGCs) found in devastating plant pathogens and biocontrol fungi revealed an uncharacterized and conserved polyketide BGC. Genome mining identified the associated metabolite to be treconorin, which has a terpene-like, trans-fused 5,7-bicyclic core that is proposed to derive from a (4 + 3) cycloaddition. The core is esterified with Dglucose, which derives from the glycosidic cleavage of a trehalose ester precursor. This glycomodification strategy is different from the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Genome mining of agriculturally relevant fungi, such as the Trichoderma species has identified a conserved polyketide biosynthetic gene cluster that produces treconorin 24 , a glycosylated natural product, which contains a 5,7-bicyclic polyketide core. 24 Investigation of the key enzymes revealed that treconorin is formed via a novel glycosylation process, involving glycosidic cleavage of a trehalose ester precursor. An in vitro approach has been used to characterise the α-hydroxylation bimodule of the mupirocin biosynthetic pathway, responsible for the installation of the 6-hydroxy group of pseudomonic acid A 25 .…”
mentioning
confidence: 99%
“…Genome mining of agriculturally relevant fungi, such as the Trichoderma species has identified a conserved polyketide biosynthetic gene cluster that produces treconorin 24 , a glycosylated natural product, which contains a 5,7-bicyclic polyketide core. 24 Investigation of the key enzymes revealed that treconorin is formed via a novel glycosylation process, involving glycosidic cleavage of a trehalose ester precursor. An in vitro approach has been used to characterise the α-hydroxylation bimodule of the mupirocin biosynthetic pathway, responsible for the installation of the 6-hydroxy group of pseudomonic acid A 25 .…”
mentioning
confidence: 99%